2001
DOI: 10.1111/j.1745-7599.2001.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Worth Their Weight in Gold: The Role of Clinical Coordinator in a Family Nurse Practitioner Program

Abstract: Implications for PracticeIt is important that this complex and valuable role be better understood and appreciated by university administrators and other faculty. Clinical coordination in a distance learning program can take up to three fourths release time for a faculty. The role of the clinical coordinator is diverse, not easily learned, and requires proficiency in academic advising, administration, and clinical supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“… Compiled from Amelia et al, 2001; Haussler, 2001; Hayes, 1994; Lyon & Peach, 2001; NONPF, 2000; Sobralske & Naegele, 2001. …”
Section: The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“… Compiled from Amelia et al, 2001; Haussler, 2001; Hayes, 1994; Lyon & Peach, 2001; NONPF, 2000; Sobralske & Naegele, 2001. …”
Section: The Literaturementioning
confidence: 99%
“…A considerable body of literature exists in which the authors have cited examples of supports and resources critical to the faculty-student-preceptor triad (Amelia et al, 2001;Gibson & Hauri, 2000;Hildebrandt, 2001;Lyon & Peach, 2001;NONPF, 2000;Sobralske & Naegele, 2001). These are detailed in Table 2.…”
Section: The Literaturementioning
confidence: 99%
“…Their study found that the majority of academic clinical coordinators were not tenure eligible, partly due to the extensive demands of the position, and recommend their effectiveness be evaluated differently and by those with whom they interact the most when carrying out tasks (Buccieri and Brown 2006). Similarly, Sobralske and Naegele (2001) describe the nurse practitioner clinical coordinator role as complex, acknowledging that the value of the role is not clearly understood by administrators or by clinical coordinators themselves. They propose that the difficulty in understanding is due to associated multifaceted duties and the competencies needed for effectiveness (i.e., clinical, academic, and scholarship competence), as well as personal qualities such as creativity, flexibility, and communication skills.…”
Section: Complexity Of the Rolementioning
confidence: 92%
“…Additionally, 64% of Stickler's survey participants did not have written job descriptions, role tasks, or functions (Strickler, 1991, p. 6). Nurse practitioner clinical coordinator responsibilities include working with students and clinical faculty to resolve conflict, which entails communication skills, flexibility, and creativity (Sobralske and Naegele, 2001).…”
Section: Tasks Of the Rolementioning
confidence: 99%
“…The lack of preceptors is noted to be one reason nearly 30 percent of nursing programs cite for turning away qualified applicants to their programs [12]. Sobralske and Naegele believe "finding clinical sites and qualified NP preceptors is the biggest challenge for FNP programs and is a time consuming and costly endeavor" [13].…”
Section: Unique Challenges For Online Programsmentioning
confidence: 99%